The efficiency of the psychological training in the system of training of young judoists - Kurylyuk S.I; Fotuyma O.Ya (Kharkov National Pedagogical University, 2010)
The rich in content side of organization and leadthrough of psychological training is described. Psychological training is intended for trainings employments of judoists of the initial stage of preparation in the annual loop. The important criterion of optimization of psychological, technical, tactical and physical preparation of judoists is formed of their psychomotor processes. Functional mobility, force of the nervous system, latent period, is selected, simple and difficult visile-motor reaction.